Predicting Future Years of Life, Health, and Functional Ability: A Healthy Life Calculator for Older Adults. (6th October 2015) - Diehr, Paula; Diehr, Michael; Arnold, Alice; Yee, Laura M.; Odden, Michelle C.; Hirsch, Calvin H; Thielke, Stephen; Psaty, Bruce M.; Johnson, W. Craig; Kizer, MD, Jorge R.; Newman, Anne
Objective: To create personalized estimates of future health and ability status for older adults.Method: Data came from the Cardiovascular Health Study (CHS), a large longitudinal study. Outcomes included years of life, years of healthy life (based on self-rated health), years of able life (based on activities of daily living), and years of healthy and able life. We developed regression estimates using the demographic and health characteristics that best predicted the four outcomes. Internal and external validity were assessed.Results: A prediction equation based on 11 variables accounted for about 40% of the variability for each outcome. Internal validity was excellent, and external validity was satisfactory. The resulting CHS Healthy Life Calculator (CHSHLC) is available athttp://healthylifecalculator.org .Conclusion: CHSHLC provides a well-documented estimate of future years of healthy and able life for older adults, who may use it in planning for the future.